Energy Efficiency Analysis in the Case of Sustainable Lighting Design Butterfly Valley Park (Konya) - Zekeriya Can Erbil; Nurgül Arısoy (Turkish Journal of Agriculture: Food Science and Technology)
The concept of lighting is of great importance in providing the security that people need so that they can have a quality of life and in meeting their aesthetic needs. Lighting design is related to the physical structure and the environment, and thanks to the lighting design, the aesthetic and functional needs of people will be met and the quality of life will be increased. The need to reflect the historical, cultural and aesthetic values of the city has brought the issue of urban lighting to the agenda. Lighting systems, which are applied without paying attention to the necessary lighting standards and criteria, cause some problems in urban spaces. One of these problems is light pollution; It is generally defined as the use of light in the wrong place, in the wrong amount, in the wrong direction and at the wrong time. Light pollution adversely affects the natural life and daily lives of people, and it is necessary to take various measures to eliminate such negativities in human life, to detect and eliminate these problems. In this study; The standards for the lighting of the city parks obtained by the literature studies were determined, the current lighting situation of the Butterfly Valley Park and the recommended lighting design produced by the Relux software in accordance with the standards. According to the findings; In the current lighting project, the total power consumed as a result of the lighting of all the lamps of the area has been calculated as 96 005.0 W. In the proposed lighting project, the total power consumed as a result of the burning of all lamps was calculated as 27 630.0 W. The obtained energy gain was found to be 96 005.0 W – 36 700.0 W = 68 375.0 W. As a result of working in the light of this information, energy savings of 1 in 3 have been achieved.